Psikologis Tokoh dalam Novel The Hidden Reality Karya Shannin serta Relevansinya terhadap Pembelajaran Menganalisis Isi dan Kebahasaan di SMA - Lazarus Linarto; Yunita Sari; Misnawati Misnawati; Patrisia Cuesdeyeni (Universitas Palangka Raya, 2025)
This study aims to (1) describe the psychological elements present in the novel “The Hidden Reality” by Shannin, and (2) discuss the relevance of this research to the teaching of content analysis and language in high school literature classes. Employing a qualitative descriptive approach, the research sources data from the novel itself. The data collection procedures involve reading, marking, writing, and classifying information. The results indicate that 44 psychological data points can be identified within the framework of id, ego, and superego, with superego being the most dominant element. The psychological portrayal of characters in “The Hidden Reality” employs simple and easily comprehensible language and style, making it suitable for enrichment in Indonesian language education in high schools, specifically within the curriculum content standard 3.9: Analyzing the content and language of novels. This research suggests that the findings can be utilized in lesson planning and can contribute to the curriculum for analyzing the content and language of literature.